2021
DOI: 10.1080/15564886.2021.1948477
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Domestic Violence Arrests during the COVID-19 Pandemic in Miami-Dade County

Abstract: The global health crisis that started early in 2020 has triggered a surge of interest in the effect (if any) of COVID-19 (coronavirus disease) on patterns of domestic violence. The first systematic review and metaanalysis examining domestic violence during the pandemic revealed quite a lot of diversity in the approaches used to measure potential effects. Drawing on the time series forecasting literature, this brief report contributes to the growing body of evidence around the issue of domestic violence during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some other studies, however, observed no significant changes in DV incidents after stay-at-home policies were implemented (Ashby, 2020 ; Campedelli et al, 2020 ; Shayegh & Malpede, 2020 ) while others reported a sharp decline (Halford et al, 2020 ) or a consistent increase (Ravindran & Shah, 2020 ). Conversely, a more recent study with a larger post-lockdown window did find some increase in DV but the overall trend was relatively stable (Piquero et al, 2021b ).…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…Some other studies, however, observed no significant changes in DV incidents after stay-at-home policies were implemented (Ashby, 2020 ; Campedelli et al, 2020 ; Shayegh & Malpede, 2020 ) while others reported a sharp decline (Halford et al, 2020 ) or a consistent increase (Ravindran & Shah, 2020 ). Conversely, a more recent study with a larger post-lockdown window did find some increase in DV but the overall trend was relatively stable (Piquero et al, 2021b ).…”
Section: Literature Reviewmentioning
confidence: 90%
“…To date, several empirical studies which conducted short-term time-series analyses of DV patterns in relation to pandemic-induced lifestyle changes have provided mixed findings. Piquero et al ( 2021b ) used an intervention time-series methodology to track changes in DV incident counts in Dallas, TX and found a short-term increase in the first two weeks after lockdown and a decline thereafter. Similarly, Leslie & Wilson ( 2020 ) and Silverio-Murillo et al ( 2020 ) studied variations in 14 U.S. cities and Mexico City, Mexico, respectively, and found evidence for a short-term increase in incidents and a subsequent return to pre-COVID rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The longer follow up period is important because it allows us to examine not just the effects of the stay-at-home restrictions on crime, but also to identify the short-term effects of various phases of re-opening (cf. Campedelli et al, 2020; Piquero, Piquero, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Piquero and colleagues (Piquero et al, 2020 , 2021a , 2021b ; Reingle Gonzalez et al, 2020 ) have written a series of articles exploring impact of COVID-19 on domestic violence, finding an increase in incidents across several geographic areas at least in the first few weeks after the lockdowns were initiated. Similarly, Nix and Richards ( 2021 ) found increases in calls to the police for domestic violence in five of the six jurisdictions studied.…”
Section: Literature Reviewmentioning
confidence: 99%